1 GHz fundamental repetition rate thulium-doped all-polarization maintaining modelocked fiber laser - Cuadrado Laborde, Christian Ariel (2024)
In this work, we present a passively modelocked all-fiber laser that fully retains polarization with a fundamental repetition rate of 1 GHz. The whole cavity consists of a 106 mm-long highly-Tm-doped polarization-maintaining fiber with a dichroic mirror on one end and a semiconductor saturable absorber mirror on the other. We experimentally characterized the output of this laser, which emits a train of transform-limited light pulses with a temporal width of 520 fs at the central optical wavelength of 1.96 μm. The high stability of this laser was also experimentally verified. Together with this, a detailed theoretical model was developed, confirming the experimental results.